Brexit and the Control of Tobacco Illicit Trade. - Foltea, Marina (SpringerBriefs in Law, 2020)
This book assesses the consequences of Brexit for the control of illicit trade in tobacco products in the UK and EU. Based on the currently applicable legal framework, it examines the significance of a possible non-application of the acquis communautaire in the UK in matters relating to anti-illicit trade in tobacco legislation. It also analyses the modes of future cooperation between the UK and the EU in this area, as well as possible regulatory scenarios and their consequences. The book comprises six main sections. After the introduction (Section 1), Section 2 discusses the state of play of Brexit and possible outcomes of Article 50 of the Treaty of European Union procedure. Section 3 illustrates the data and trends of illicit tobacco trade in the UK. Section 4 describes the relevant legal (e.g. trade and fiscal measures) and enforcement frameworks in the UK and suggests possible post-Brexit scenarios in control of tobacco illicit trade. Section 5 focuses on the relevance of arrangements between governments and the tobacco industry in the control of illicit trade. Section 6 then analyses the relevance of key EU and global anti-illicit trade initiatives. Lastly, Section 7 the book offers some recommendations and conclusions on how the UK could control illicit trade in tobacco after Brexit.